The Memoirs of Harry S. Truman : A Reader's Edition - Truman, Harry S., 1884-1972 (Book collections on Project MUSE., 2019)
"Raymond H. Geselbracht's new edition of Harry S. Truman's memoirs, which reduces the length and greatly clarifies the presentation of the original memoirs' text, offers a new generation of readers the thrill of hearing the unique and authentic voice of Harry S. Truman, probably the most important president of the last seventy-five years, telling the story of his life, his presidency, and some of the most important years in American history"--